Service Quality Assessment of Travel Agency O2O Model Based on Improved Evidence Theory. Issue 5 (2nd September 2020) - Shi, Ping-Ping; Hu, Yaogang
ABSTRACT: A method of service quality from tourists' perception based on improved evidence theory is proposed, because it is difficult to obtain the effective service quality of travel agency O2O model by using the existing traditional assessment methods with the weights of assessment indices. Firstly, from online purchasing and offline experience, the service quality indices of travel agency O2O model are subdivided, and a framework for assessing service quality is constructed. Secondly, according to the evidence theory and amendment idea of evidence sources, the high-conflict problem among the evidences is solved, and the service quality assessment method is proposed. Finally, the proposed method is used to assessment service quality based on the survey data of a certain travel agency O2O model. By comprising with the traditional assessment method, the results show that the high-conflict problem can be solved, and the proposed model is correct and effective for assessing service quality.